2019
DOI: 10.3389/fneur.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cognitive and Motor Skills in Parkinson's Disease by a Robotic Object Hitting Game

Abstract: Parkinson's disease (PD) patients experience various symptoms including extrapyramidal motor disturbances and cognitive impairments, which cause difficulties in daily life. However, PD patients have rarely been studied under realistic task situations that require high-level interaction of cognitive and motor skills. The aim of this study was to investigate the contribution of cognitive and motor factors to the performance of PD patients under high cognitive and kinematic loads. Twenty-six PD patients and 14 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…In both the object hit task and object hit and avoid task , mean hand speed and limb asymmetries showed high discriminatory abilities in differentiating subjects with PD from healthly controls. Our findings support similar observations of mean hand speed by Wiratman et al [43] using the KINARM object hit and avoid task . Mean hand speed and limb asymmetries had significant correlations with UPDRS bradykinesia scores when subjects were OFF medication.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In both the object hit task and object hit and avoid task , mean hand speed and limb asymmetries showed high discriminatory abilities in differentiating subjects with PD from healthly controls. Our findings support similar observations of mean hand speed by Wiratman et al [43] using the KINARM object hit and avoid task . Mean hand speed and limb asymmetries had significant correlations with UPDRS bradykinesia scores when subjects were OFF medication.…”
Section: Discussionsupporting
confidence: 93%
“…This increase was inversely correlated with a reduction in UPDRS cumulative scores. The increase in distractor hits relative to controls is consistent with a recent study by Wiratman et al [43] using the KINARM that demonstrated that patients with poor performance on standard cognitive batteries had higher distractor hits. In the present study no correlations were observed with MoCA scores but this may be due to limitations in using the MoCA to quantify cognitive function in subjects with PD.…”
Section: Discussionsupporting
confidence: 90%
“…The Kinarm robotic assessment system (Kinarm, Kingston, ON, Canada) is a tool that quantifies performance on a collection of behavioral tasks that test motor, cognitive, and sensory functions, referred to as Kinarm Standard Tests™ (KSTs). It has been used to characterize deficits in a variety of clinical populations such as stroke ( [14][15][16]), ALS [17], Parkinson's disease [18], TIA [19], and concussion [20]. Furthermore, previous work has highlighted the test-retest reliability of Kinarm assessment results [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported an association between hand fine motor skill disability and cognitive dysfunction severity [ 10 , 11 , 12 ]. Unlike AD, where memory impairment is the core symptom of dementia, the cognitive dysfunction profile in PD is heterogeneous, influencing various domains of executive function, spatial cognition, psychomotor speed, and memory [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%